2020
DOI: 10.1371/journal.pone.0236151
|View full text |Cite
|
Sign up to set email alerts
|

Cooking fuels use and carotid intima-media thickness during early pregnancy of women in Myanmar

Abstract: Background Fuels burned in households for cooking cause indoor air pollution, exposing those who are cooking. Despite the mounting evidence of the effects of fuels use on health, few studies focus on the effect of cooking fuels have on carotid intima-media thickness (CIMT), a surrogate atherosclerosis biomarker in the early stages of pregnancy. This study aimed to examine the association between the use of cooking fuels and CIMT during early trimester of pregnancy among cooking women in Myanmar. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In addition to PM 2.5 , we further demonstrate long-term exposure to certain transition metals of PM 2.5 , namely Mn, Fe, and Zn, are associated with higher CIMT values. Epidemiological studies have demonstrated speci c human activities, such as residing tra c proximity and cooking fuels, are associated with increased CIMT measures [11,12,27,28]. Certain source-speci c components of PM, including organic carbon, elemental carbon, black carbon, and S were reported to associate with increased CIMT values in elderly population [12,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PM 2.5 , we further demonstrate long-term exposure to certain transition metals of PM 2.5 , namely Mn, Fe, and Zn, are associated with higher CIMT values. Epidemiological studies have demonstrated speci c human activities, such as residing tra c proximity and cooking fuels, are associated with increased CIMT measures [11,12,27,28]. Certain source-speci c components of PM, including organic carbon, elemental carbon, black carbon, and S were reported to associate with increased CIMT values in elderly population [12,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%